,

   ,

   ,

   , 3



. 20 :

(H = Mh x n)

H1 , (H1 = Mh - b)

H2 - , (2 = Mh + b);

Mh (Mh = h + b); b - ; h ()

250 120 65 (.)

b ,

(Mh, H, H1, H2) 250 120 65 (h); ( )

Mh

H

H1

H2

Mh = h + b

H = Mh

H1 = (Mh x n)-b

H2 = (Mh x n)+b

8

65 + 8 = 73

H = Mh

H1 = (Mh x n)-8

H2 = (Mh x n)+8

10

65 + 10 = 75

H = Mh

H1 = (Mh x n)-10

H2 = (Mh x n)+10

12

65 + 12 = 77

H = Mh

H1 = (Mh x n)-12

H2 = (Mh x n)+12

15

65 + 15 = 80

H = Mh

H1 = (Mh x n)-15

H2 = (Mh x n)+15

250 120 88 (h)

6 ,

(Mh, H, H1, H2) 250 120 65 (h); ( )

Mh

H

H1

H2

Mh = h + b

= Mh x n

H1 = (Mh x n) - b

H2 = (Mh x h) + b

8

88 + 8 = 96

= Mhx n

H1 = (Mh x n) - 8

H2 = (Mh x h) + 8

10

88 + 10 = 98

= Mhx n

H1 = (Mh x n) - 10

H2 = (Mh x h) + 10

12

88 + 12 = 100

= Mhx n

H1 = (Mh x n) - 12

H2 = (Mh x h) + 12

15

88 + 15 = 103

= Mhx n

H1 = (Mh x n) - 15

H2 = (Mh x h) + 15

250 120 138 (h)

b ,

(Mh, H ,H1, H2) 250 120 65 (h);

(n )

Mh

H

H1

H2

Mh = h + b

H = Mh x n

H1 = (Mh x n) - b

H2 = (Mh x n) + b

8

138 + 8 = 146

H = Mh x n

H1 = (Mh x n) - 8

H2 = (Mh x n) + 8

10

138 + 10 = 148

H = Mh x n

H1 = (Mh x n) - 10

H2 = (Mh x n) + 10

12

138 + 12 = 150

H = Mh x n

H1 = (Mh x n) - 12

H2 = (Mh x n) + 12

15

138 + 15 = 153

H = Mh x n

H1 = (Mh x n) - 15

H2 = (Mh x n) + 15

:

379-95, 530-2007.

:

1. 250 120 65 (h), , 34 8 . : . 6:

= Mh = (65 + 8) 34 = 2482 .

2. 250 120 138 (h) 12 . : . 8:

H1 = (Mh x b)- b = (138 + 12) 7 - 12 = 1 038 .

3. 250 120 88 (h) 10 44 . : . 7:

H2 = (Mh x n) + 10 = (88 + 10) 44 + 10 = 4322 .

« »